ANALISIS USER EXPERIENCE PADA APLIKASI THREADS MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) - Indah Tri Handayani; Hafidzah Hafidzah; Uppit Yuliani (Jurnal Ilmiah Teknik, 2024)
This research aims to analyze the User Experience in the Threads application through the application of the User Experience Questionnaire (UEQ) method. User Experience (UX) is how users interact with a product or service offered by a company or organization. The role of users certainly greatly influences the success of an application. The Threads app is a social media app that launched on July 5, 2023, but its user experience has not been explored much. The UEQ method is used to measure various aspects of user experience, including Attractiveness, Clarity, Efficiency, Appropriateness, Stimulation, and Novelty. The research was carried out by distributing questionnaires that had been created using Google Form and then processing the data results using the Data Analysis Tool. UEQ analysis results provide deep insight into how users interact with Threads applications and how certain aspects of the user experience can be improved. Of the 6 UEQ assessment scales, the results of this research are that there are 4 scales with "Bad" results in Attractiveness, Efficiency, Accuracy, and Stimulation. Then, there is a scale with “Below Average” results in Clarity. And there is a scale with “Above Average” results in Recency. This indicates that the Threads application has a poor benchmark level. The results of the User Experience (UX) analysis show that users feel less satisfied when using the Threads social media application.